Clinical and Molecular Aspects of Senataxin Mutations in Amyotrophic Lateral Sclerosis 4. Issue 4 (28th January 2020) - Grunseich, Christopher; Patankar, Aneesh; Amaya, Joshua; Watts, Jason A.; Li, Dongjun; Ramirez, Prisila; Schindler, Alice B.; Fischbeck, Kenneth H.; Cheung, Vivian G.
Abstract : Objective: To determine the clinical and molecular features in patients with amyotrophic lateral sclerosis 4 (ALS4) due to mutations in the senataxin ( SETX ) gene and to develop tools for evaluating SETX variants. Methods: Our study involved 32 patients, including 31 with mutation in SETX at c.1166 T>C (p.Leu389Ser) and 1 with mutation at c.1153 G>A (p.Glu385Lys). Clinical characterization of the patients included neurological examination, blood tests, magnetic resonance imaging (MRI), and dual‐energy x‐ray absorptiometry (DEXA). Fibroblasts and motor neurons were obtained to model the disease and characterize the molecular alteration in senataxin function. Results: We report key clinical features of ALS4. Laboratory analysis showed alteration of serum creatine kinase and creatinine in the Leu389Ser ALS4 cohort. MRI showed increased muscle fat fraction in the lower extremities, which correlates with disease duration (thigh fat fraction R 2 = 0.35, p = 0.01; lower leg fat fraction R 2 = 0.49, p < 0.01). DEXA measurements showed lower extremities are more affected than upper extremities (average fat z scores of 2.1 and 0.6, respectively). A cellular assay for SETX function confirmed that like the Leu389Ser mutation, the Glu385Lys variant leads to a decrease in R loops, likely from a gain of function. Interpretation: We identified clinical laboratory and radiological features of ALS4, and hence they should be monitored for disease progression. The molecular characterization of R‐loop levels in patient‐derived cells provides insight into the disease pathology and assays to evaluate the pathogenicity of candidate mutations in the SETX gene. ANN NEUROL 2020;87:547–555